NIS-Mediated Oxidation of Hydrazones: A Rapid Access to Fused Lactones and Tosylhydrazides - Takallou, Ahmad; Al-Shidhani, Sulaiman; Al-Siyabi, Munir; Mobaraki, Akbar; Anwar, Muhammad U.; Al-Harrasi, Ahmed (Synlett, 2023)
A tandem one-pot strategy for the synthesis of 4-iodo-3-aryl(alkyl)-1H-pyrano[4,3-b]quinolin-1-ones and (E)-3-(iodo(phenyl)methylene)isobenzofuran-1-(3H)-ones from 2-alkynylhydrazones has been developed through oxidation and regioselective 6-endo- and 5-exo-iodocyclization pathways by using NIS as an iodinating reagent. This approach tolerates a variety of in situ generated alkynyl-containing tosylhydrazones and affords the corresponding products in high yields. The protocol has also been applied for the synthesis of different derivatives in good to excellent yields.
Keywords: tandem reactions; N-iodosuccinimide; lactones; tosylhydrazones; alkynes; oxidation